The importance of creativity in engineering education; Лингвистические и культурологические аспекты современного инженерного образования - Куимова М. В. Марина Валерьевна (2024, 2024)
Successful engineers possess not only good technical qualification and abilities, but also a range of soft skills, including leadership, emotional intelligence, communication, problem-solving, organization, creativity and more. These skills are indispensable for handling the tasks of modern engineering. This paper highlights the positive effects of using creative tasks in both engineering education and the teaching of foreign languages